Prevalence and Risk Factors of Premature Ovarian Insufficiency/Early Menopause - Giri, Rinky; Vincent, Amanda J. (Seminars in Reproductive Medicine, 2020)
Premature ovarian insufficiency (POI) and early menopause, defined as loss of ovarian activity prior to 40 years or menopause between the ages of 40 and 45 years, respectively, is associated with significant adverse health impacts. Recent data indicate that the prevalence of POI and early menopause is greater than was previously thought, affecting more than 10% of women. Biopsychosocial risk factors including genetic, autoimmune, reproductive, lifestyle, early-life, social/environmental, and iatrogenic have been associated with POI/early menopause or earlier age at menopause. However, establishing a causal role and the underlying mechanisms remains elusive. Understanding and clarification of these risk factors will facilitate prevention and risk minimization strategies to optimize women's health.
Keywords: premature ovarian insufficiency; early menopause; risk factors; prevalence